Violência e Saúde Coletiva: contribuições teóricas das ciências sociais à discussão sobre o desvio - Oliveira, Walter Ferreira de (2008)
Public Health and the Human and Social Sciences are inseparable fields of knowledge, as attested by a tradition of research groups and research lines located in Public Health post-graduate programs. Several difficulties have been pointed when discussions about various themes traditionally identified with the social sciences, as is the case of violence, are inserted in the health field. At the same time, such discussions are considered essential to the understanding of the determination of populations' health conditions and quality of life. The discussion focus regarding this phenomenon lacks theoretical contributions from other disciplines, such as Sociology, whose theories on crime and deviance constitute an important benchmark in the study of the various forms of violence. In this article, the author examines the classic sociological theories in this area, aiming to contribute to the expansion of discussion in the field of Public Health, particularly in terms of a knowledge base to be applied to health promotion, crime prevention and rehabilitation, thus considering Public Health from an interdisciplinary, intersectorial perspective.Saúde Coletiva e Ciências Sociais e Humanas são campos reconhecidamente inseparáveis, o que se afirma por uma tradição de grupos e linhas de pesquisa em programas de pós-graduação em Saúde Coletiva. Várias dificuldades têm sido apontadas, entretanto, em inserir discussões sobre temas tradicionalmente estudados nas ciências sociais, como a violência, no campo da saúde, ao mesmo tempo em que tal discussão tem sido vista como crucial para o entendimento de determinações de condições de saúde e qualidade de vida das populações. O foco de discussão sobre esse fenômeno carece de aportes teóricos de outras disciplinas, como a Sociologia, cujas teorias sobre o crime e sobre o desvio da norma constituem importante marco no estudo das violências. Neste artigo, o autor examina as teorias clássicas da sociologia nesse âmbito, buscando contribuir para a ampliação da discussão no campo da Saúde Coletiva, particularmente no que concerne a uma base de pensamento sobre a promoção, a prevenção e a reabilitação de agravos, considerando-a, assim, numa perspectiva interdisciplinar e de abrangência intersetorial